Three Different Genotyping of Mycobacterium leprae in a Family: A Case Report - Renata Mayangsari; M. Yulianto Listiawan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Indonesia is the third country with the highest prevalence of leprosy worldwide after India and Brazil. The risk of transmission is higher in household contacts, siblings, and neighborhoods. Purpose: Familial leprosy due to household contacts has been considered as the main transmission in leprosy. The aim of the examination is to detect the presence of Mycobacterium leprae and analyze the variation number of TTC repeats. Case: A family, consisted of mother, 35 year-old, was diagnosed with lepromatous leprosy (LL) type and erythema nodosum leprosum (ENL) necroticans. Her husband, 36 year-old, was diagnosed with tuberculoid leprosy. Daughter, 4 year-old, was diagnosed as indeterminate leprosy due to white small patches on her left cheek, arm, and leg, but there was no complain about anesthesia. Case management: Enzyme-linked immunosorbent assay (ELISA), histopathological examination, and polymerase chain reaction (PCR) for detection of M. leprae were performed. All of PCR results were positive. After sequencing of the TTC area, it revealed that the number of TTC repeats were different. Conclusion: Transmission from mother to others was suspected in family with leprosy living in the same house. PCR examination revealed 16 times TTC repeats on mother, 18 times on father, and 13 times on daughter. It was proven that infection of M. leprae originated from different genomes, which means different source of infection.